Phenotypic characterisation of mice with exaggerated and missing LH/hCG action - Ahtiainen, Petteri (2007)
In order to study the physiology and pathophysiology of gonadotrophin action, we have produced transgenic (TG) mice overexpressing human chorionic gonadotrophin (hCG) alpha and beta subunits (hCG+ mice) and knockout (KO) mice for the luteinising hormone receptor (LHR; LuRKO mice). The two extremes in LH function, i.e. strong LH/hCG stimulation and total blockade of this action, confirm numerous earlier concepts about LH function, but they also reveal new aspects about gonadal function during excessive LH production and in the absence of this trophic stimulus. The purpose of this review is to summarise the key findings on these two genetically modified mouse models.